Study of Diesel Engine Performance Using Variations of Dexlite Fuel Mixture and Corn Seed Oil - Samuel JW Siagian (Trigin Publisher, 2022)
Due in the world population continues to increase so the need for fossil fuels also increased. This is what requires us to look for other sources beyond oil and gas, or that can be said alternative fuel. Alternative fuel not only to solve the scarcity problem but also a problem of air pollution caused by fossil fuels. This alternative fuel can be obtained from the seeds of the rubber, corn, tobacco, oil seeds, sunflower seeds, and others where at designated for diesel engines. This study aims is to analyze the performance of TD–115. From this Research diesel engine using corn biodiesel mixture Dexlite fuel by using (Dexlite, Dexlite + 5% Biodiesel, Dexlite + 10% Biodiesel, Dexlite + 15 % Biodiesel, Dexlite + 20% Biodiesel, Dexlite + 25% Biodiesel). Found that the Power (P) decrease up to 40, Specific Fuel Consumption (SFC) of the mixture increase up 48 Thermal Actual Brake Efficiency ( decrease up to 41%, rate of mass fuel (mf) decreased to 59%, Volumetric Efficiency ( ) decreases to 19%, Heat Losses decrease up to 74%, Air Fuel ratio decreased to 44%.